2022
DOI: 10.1021/acs.iecr.2c01066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Role of Noble Metal Nanoparticles (Pt and Pd) on the Photocatalytic Performance of the BaFe12O19/TiO2 Magnetic Nanocomposite: Green Synthesis, Characterization, and Removal of Organic Dyes under Visible Light

Abstract: Adding noble metals and barium hexaferrite to TiO 2 creates novel magnetic plasmonic nanocomposites with high activity in the photodegradation of organic contaminants. In this work, we have synthesized BaFe 12 O 19 by microwave and sol−gel combustion (using green fuel, glucose) methods and TiO 2 by the sol−gel method. Then, noble metals (Pt and Pd) were deposited on BaFe 12 O 19 /TiO 2 by a reducing agent (glucose: green surfactant) under ultrasound waves. The samples were characterized. On the basis of XRD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…As previously observed by Suthar et al, the substitution of La 3+ ions for Ba 2+ ions cause the introduction of Fe 2+ ions into the structure, which leads to a reduction in M s from 38.53 to 33.71 emu g −1 and an increase in coercivity (H c ) from 94.17 to 213.30 Oe [54]. Razavi et al [55] recently found a decrease in the saturation magnetization (M s ). According to Anjum et al, saturation magnetization reduced as Sr +2 ion content increased, and this reduction was caused by the various sites that Sr +2 and Fe +3 ions occupied [26].…”
Section: Magnetic Measurementmentioning
confidence: 67%
“…As previously observed by Suthar et al, the substitution of La 3+ ions for Ba 2+ ions cause the introduction of Fe 2+ ions into the structure, which leads to a reduction in M s from 38.53 to 33.71 emu g −1 and an increase in coercivity (H c ) from 94.17 to 213.30 Oe [54]. Razavi et al [55] recently found a decrease in the saturation magnetization (M s ). According to Anjum et al, saturation magnetization reduced as Sr +2 ion content increased, and this reduction was caused by the various sites that Sr +2 and Fe +3 ions occupied [26].…”
Section: Magnetic Measurementmentioning
confidence: 67%
“…The excess of dye prevents the penetration of light through the successive layers of dye onto (AAc-g-AM)/TiO 2 hydrogel surface is weak to generate the required excited state of the dye on (AAc-g-AM)/TiO 2 hydrogel. 17 The dye concentration 40 mg/L gives the best Photocatalytic degradation capacity (77.49%). [18][19][20][21] The data of the change in (PDE%)with GR dye appear in Figure 5.…”
Section: Effect Of Cr Dye Concentrationmentioning
confidence: 97%
“…of MB dye 80 mg/L gave better photocatalytic efficiency (87.88%). 27,30,31 The result of the change in (PDE%) with MB appears in Figure 7.…”
Section: Effect Concentration Of Mb Dyementioning
confidence: 99%